Radiofrequency ablation versus surgical resection in elderly patients with early-stage hepatocellular carcinoma in the era of organ shortage - Bin Yu; Youming Ding; Xiaofeng Liao; Changhua Wang; Bin Wang; Xiaoyan Chen (The Saudi Journal of Gastroenterology, 2018)
Background/Aims: To compare the survival benefits of surgical resection (SR) with those of radiofrequency ablation (RFA) in elderly patients (≥65 years) with single hepatocellular carcinoma (HCC) ≤5 cm. Patients and Methods: Using the Surveillance, Epidemiology, and End Results database, a total of 461 patients who underwent SR and 575 patients who underwent RFA were enrolled from 2004 to 2012. Overall survival (OS) and liver-cancer-specific survival (LCSS) comparisons were conducted between the two groups before and after propensity score matching (PSM).Results: Elderly patients with early-stage HCC had a lower rate of utilization of liver transplantation, and they were more likely to receive SR or RFA as their first-line treatment compared with younger patients (P < 0.05). In the whole cohort, the SR group had significantly better OS [RFA, hazard ratio (HR) = 1.680 (1.390, 2.031), P < 0.001] and LCSS (RFA, HR = 1.658 (1.327, 2.070), P < 0.001) than the RFA group. After PSM, the improved survival in the SR group was further confirmed (all P < 0.001). In the subgroup analyses, according to patients' age (65–75, >75 years) and tumor size (≤3.0, 3.1–5.0 cm), the SR group still presented better OS and LCSS than the RFA group (all P < 0.05), except for those older than 75 years with tumors ≤3.0 cm (all P > 0.05), both before and after PSM. Conclusion: Treatment strategies for elderly patients (≥65 years) with single HCC ≤5 cm should emphasize SR as the primary therapy, while RFA can be an alternative to SR for those> 75 years with single HCC ≤3 cm.